Effect of Different Levels of Nitrogen, Phosphorus And Potassium on the Growth and Yield of Cucumber (Cucumis Sativus L.) In the Coastal Region of Bangladesh - Ali, Md Sabuj; Majumder, Dipta; Hasan, Rakib; Aff, Tawseef Al; Mohammad, Nur; Hossen, Kawsar (Research in Agriculture Livestock and Fisheries, 2022)
The experiment was carried out at Agricultural Research Field, Noakhali Science and Technology University, Noakhali, Bangladesh during the period of March to June 2021, to evaluate the growth and yield of cucumber (Cucumis sativus L. CV: MOHABIR) as influenced by different levels of NPK fertilizer. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. The treatments were T0 (no NPK), T1 (N 69 kg ha-1, P2O5 48 kg ha-1 and K2O 75 kg ha-1), T2 (N 69 kg ha-1, P2O5 60 kg ha-1 and K2O 90 kg ha-1), T3 (N 92 kg ha-1, P2O5 72 kg ha-1 and K2O 105 kg ha-1), respectively. Data were recorded from different stages of plant growth on the number of leaves per plant, number of fruits per plant, fruit length, fruit diameter, individual fruit weight, yield per plant and yield per plot. All the recorded parameters were statistically significant (p<0.01). The maximum number of leaves per plant (37.83) was recorded from T3 (N 92 kg ha-1, P2O5 72 kg ha-1 and K2O 105 kg ha-1) whereas the minimum number of leaves per plant (27.92) was obtained from the control T0 (no NPK). Highest number of fruits per plant (11.92), fruit length (16.00 cm), fruit diameter ((4.10 cm), individual fruit weight (167.17 g), weight of fruits per plant (2.00 kg), and yield per hectare (68.35 t/ha) was found in treatment T3 (N 92 kg ha-1, P2O5 72 kg ha-1 and K2O 105 kg ha-1) whereas lowest data recorded from control T0 (no NPK). Observing the results, it can be stated that application of NPK fertilizer @ N 92 kg ha-1, P2O5 72 kg ha-1 and K2O 105 kg ha-1 for cucumber cultivation gave better growth and yield in the coastal region of Bangladesh. Vol. 9, No. 2, August 2022: 117-123